Can Job Satisfaction Mediate the Relationship between Emotional Intelligence and Spiritual Intelligence on Teacher Performance? - Efendi, Efendi; Harini, Sri; Simatupang, Sudung; Silalahi, Marto; Sudirman, Acai (Journal of Education Reseach and Evaluation, 2021)
This study aims to analyze the role of job satisfaction in mediating the relationship between emotional intelligence and intellectual intelligence on the performance of the high school teachers. This study uses a research design with an associative quantitative approach. Data was collected through documentation and online questionnaires. This study used a sample of 39 respondents with the determination of the sample size using the saturated sample formula. Partial least square is applied to examine the relationship between teacher performance, job satisfaction, emotional intelligence and intellectual intelligence. The results of this study indicate that of the seven hypotheses developed there are two accepted hypotheses, that is, for the effect of emotional intelligence on job satisfaction, it is obtained that the results of a significant effect and the influence of spiritual intelligence on teacher performance are also obtained significant results. Meanwhile, the other 5 hypotheses developed were not significant. Through the findings of this study, it is hoped that it can provide additional information for various parties, especially the school, to pay attention to the factors that affect teacher performance and job satisfaction, so that teachers gain comfort and confidence to continue to improve their performance in implementing learning in schools.